SOURCES ABOUT THE RULERS OF THE CHANCELLERY OF THE TURKESTAN GOVERNOR-GENERAL (World Bulletin of Social Sciences, 2024)
If the office of the Governor-General in the system of the Military People's Administration of the Turkestan government was the heart of this colonial body, then its rulers can be considered an analytical center. This article analyzes information on the history of the rulers of the Turkestan Governor-General.